1994
DOI: 10.1007/bf01695033
|View full text |Cite
|
Sign up to set email alerts
|

Results of conventional-dose cytosine arabinoside and idarubicin in elderly patients with acute myeloid leukemia

Abstract: Conventional-dose Ara-C (200 mg/m2 d 1-5) combined with idarubicin (12 mg/m2 d 1-3) was employed as remission induction and consolidation therapy in 23 elderly AML patients with a median age of 66 years (range, 60-75) with AML according to the FAB criteria (M1 n = 3, M2 n = 10, M4 n = 6, M5 n = 2, M6 n = 2), eligible for the study. In seven patients earlier MDS had been documented by previous bone marrow aspirates. The CR rate after one induction course was 65% (15/23). Toxicity was acceptable, with four patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…29,30 Idarubicin also induced a higher complete remisson rate 4,29,31,32 in older patients. 33 Maintenance of complete remission after remission-induction therapy for AML can be achieved by intensive consolidation therapy followed by allogeneic or autologous stem cell transplantation or by chemotherapy. 8,[12][13][14] Allogeneic BMT usually results in the highest disease-free survival, but its use is limited to younger patients with HLA-identical siblings.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Idarubicin also induced a higher complete remisson rate 4,29,31,32 in older patients. 33 Maintenance of complete remission after remission-induction therapy for AML can be achieved by intensive consolidation therapy followed by allogeneic or autologous stem cell transplantation or by chemotherapy. 8,[12][13][14] Allogeneic BMT usually results in the highest disease-free survival, but its use is limited to younger patients with HLA-identical siblings.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Why do older patients with AML have such a poor prognosis? Older AML patients may be relatively "undertreated" compared to younger patients, 2 or there may be significant differences between the molecular biology of AML in older patients and younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a number of recent studies have reported complete remission (CR) rates > 50% in patients aged 5 60 treated with specifically designed combination chemotherapy regimens. This may indicate that aggressive chemotherapy represents the best treatment for selected elderly patients (Ferrara et al, 1992;Heyll et al, 1994;Leoni et al, 1995;Liu Yin et al, 1991). However, selection bias may have accounted for favourable results reported in some of the studies, as confirmed by the well-documented lower inclusion rate of elderly patients in multicentre trials as compared to younger persons (Baudard et al, 1994).…”
mentioning
confidence: 99%